Cough Variant Asthma in Medical Outpatient Department of a Tertiary Care Hospital in Bangladesh - Bhattacharjee, Swapna; Bhattacharjee, Shekhar; Parvin, Rukhsana (Journal of Enam Medical College, 2013)
Background: Cough variant asthma (CVA) is a subset of asthma where the only symptom is chronic persistent cough. Many cases go unrecognized due to lack of proper evaluation. Response to asthma medication with features supportive of airway hypersensitivity helps in management of this disease. Objective: To find out the proportion of cough variant asthma among the patients attending medicine outpatient department of Enam Medical College, Savar, Dhaka. Materials and Methods: This cross sectional study was conducted in Enam Medical College Hospital, Savar, Dhaka over a period of two years from July 2009 to July 2011. Cough variant asthma was diagnosed mainly on clinical ground as chronic cough without wheezing, fever, weight loss, shortness of breath or sputum or any other apparent cause that persisted for more than eight weeks with absolutely normal physical examination of chest, normal chest radiography and blood count except raised eosinophil count and IgE level. Patients who met these criteria were given 2 weeks course of inhaler beclomethasone propionate and were assessed for improvement. Those who improved after steroid inhalation were categorised as having cough variant asthma. Results: Out of purposively selected 148 patients complaining only of chronic dry cough for more than eight weeks, 92 patients met the primary selection criteria for cough variant asthma. These 92 patients were given 2 weeks trial of 250 ìgm beclomethasone inhalation twice daily. Seventy nine patients reported almost complete recovery from chronic cough after 2 weeks and were categorized as having CVA. Thirteen patients did not improve and were not categorized as CVA. Conclusion: These findings suggest that cough variant asthma is the most common among the patients with chronic cough not due to any apparent cause. The efficacy of inhaled corticosteroid suggests that early intervention is effective in the treatment of this disease. DOI: http://dx.doi.org/10.3329/jemc.v3i1.13871 J Enam Med Col 2013; 3(1): 29-31